2017
DOI: 10.1111/echo.13764
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical left ventricular systolic and diastolic dysfunction in type 1 diabetic children and adolescents with good metabolic control

Abstract: The results of this study showed that the diabetic children and adolescents with good metabolic control had diastolic dysfunction when assessed with either conventional or tissue Doppler echocardiography. Also diabetic patients had subclinical LV systolic dysfunction with a normal LVEF which can be detected with 2D speckle tracking echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
4
24
0
1
Order By: Relevance
“…13 As in the present study, there was no LVEF difference between severe and nonsevere CAD patients. Most used methods are checking for regional wall-motion anomalies or LVEF.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…13 As in the present study, there was no LVEF difference between severe and nonsevere CAD patients. Most used methods are checking for regional wall-motion anomalies or LVEF.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies had shown that LVEF is not a sensitive marker for subclinical dysfunction. 13 As in the present study, there was no LVEF difference between severe and nonsevere CAD patients. (61.4 ± 2.94 vs 62.1 ± 3.55 P: 0.742).…”
Section: Discussionsupporting
confidence: 63%
“…27 In previous studies, LVEF was not found to be significantly different in T1DM patients compared with normal controls. [15][16][17][18]28 These findings suggest that LVEF decreases in the late period after the onset of T1DM. On color Doppler echocardiography, the A-wave velocity and e' in the D3 group decreased compared with the C3 group, which was similar to the results from previous reports.…”
Section: Conventional Parametersmentioning
confidence: 74%
“…Bu süreç, hipergliseminin sürekli olması durumunda kardiak disfonksiyon gelişimine zemin hazırlamaktadır [20]. İyi glisemik kontrollü Tip 1 diyabetli çocuk ve adolesanlarda yapılan bir çalışmada dahi sol ventrikül diyastolik fonksiyonlarında azalma olduğu bulunmuştur [21]. Asemptomatik olan tip 1 diyabetli çocuklarda yapılan bazı çalışmalarda, subklinik olarak sol ventrikül sistolik fonksiyonunun göstergesi olan EF değerinde anlamlı azalma olduğu gösterilmiştir.…”
Section: Discussionunclassified